(untitled) (Gestão & Regionalidade, 2015)
This study aimed to analyze the behavior of exchange rate pass-through mechanisms for regional inflation over inflation targeting in Brazil. Two flexibilities regarding traditional pass-through coefficient models were used for this. First, we departed from analysis at regional levels to assess which areas were the most sensitive to currency devaluations. After, the general index of each regional inflation was broken in each of the groups that composes it to assess the behavior of pass-through mechanism under a regional disaggregated perspective. The obtained empirical evidence suggests an asymmetric behavior between regions and between the groups that compose the regional indexes.